LAND AND BUILDING TAX COLLECTION AND PAYMENT MECHANISM IN MAKASSAR REGIONAL REVENUE AGENCY - Mariana, Lina (Jurnal Ekonomi Balance, 2019)
This research paper aims to determine the mechanism of billing and payment of land and building taxes at Badan Pendapatan Daerah, considering that the earth tax and buildings have been transferred to local taxes and newly operated in early 2015. This research used the qualitative descriptive method  that is the type of research used by the research to describe the results of observation data obtained. The results showed that the mechanism of billing and payment of land and building tax begins with the issuance of Tax Return Notification (SPPT). The taxpayer may obtain the Notice of Withholding Tax to the service of the integrated unit or tax collector of the land and building and then pay the tax payable. Payment can be made through POS office, or via online through Automated Teller Machine (ATM) or Bank which has been appointed by City Revenue Board of Makassar.